VD_FINDINFO HC / 2011 / 595 vom 26. Oktober 2011 - VD Tribunal cantonal (2011)
CURATELLE, CURATELLE DE REPRÉSENTATION, INDEMNITÉEN GÉNÉRAL, TARIFEN GÉNÉRAL | 392 ch. 2 CC, 417 al. 2 CC, 29 Cst., 9 Cst., 6a RTu, 319 let. a CPC (CH), 320 CPC (CH)